Climate governance and International Civil Aviation: Brazil's policy profile - Veronica Korber Gonçalves; Marcela Anselmi (Revista Brasileira de Política Internacional)
Abstract After almost 20 years, states agreed at the ICAO on the creation of Carbon Offset and Reduction Scheme for International Aviation (CORSIA). The article aims at analyzing the Brazilian role in the negotiations and presenting the debate about CORSIA in Brazil. CORSIA may encourage the expansion of offset projects in Brazil, changing local political dynamics and resulting in different environmental impacts.